2015
DOI: 10.1007/s00380-015-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Progression from stenosis to occlusion in the proximal native coronary artery after coronary artery bypass grafting

Abstract: Coronary artery bypass grafting (CABG) is an established treatment for multivessel coronary artery disease. However, problematic situations are occasionally encountered after CABG, such as disease progression in the native coronary artery with graft occlusion, which causes difficulty in revascularization. The purpose of this study was to evaluate changes in the native coronary artery after CABG. Between 2009 and 2012 in our institution, 351 patients underwent CABG, and 768 bypass grafts were anastomosed to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Cataldo et al found that the SVG patency at the end of postoperative first year was related to several angiographic factors, such as target vessel diameter and coronary territory of right coronary artery, rather than demographical characteristics of the patients [14]. SVG failure with the possible acceleration of atherosclerosis in native coronary arteries, ends up as "malign graft failure", an essential problem in the follow-up of CABG patients [4]. In our study, the presence of malign graft failures was low (3.8% of total grafted vessels).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataldo et al found that the SVG patency at the end of postoperative first year was related to several angiographic factors, such as target vessel diameter and coronary territory of right coronary artery, rather than demographical characteristics of the patients [14]. SVG failure with the possible acceleration of atherosclerosis in native coronary arteries, ends up as "malign graft failure", an essential problem in the follow-up of CABG patients [4]. In our study, the presence of malign graft failures was low (3.8% of total grafted vessels).…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of CAD in preoperatively nonoccluded native coronary arteries, was identified as the responsible factor for the development of recurrent anginal attacks in various studies. Progression of native coronary arterial disease from preoperative stenosis to postoperative total occlusion is an important feature, especially in cases of graft failure [3,4]. De novo total occlusion of a priorly non-occluded native coronary artery in the long-term postoperative period is a problematic situation, because total occlusion in CABG patients generally have a more challenging nature than chronic total occlusions (CTO) in native coronary anatomy without CABG operation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that incomplete revascularization of the LAD mainly influences the 5-10 year mortality rather than early postoperative mortality [Dourado 2018;Lawrie 1982;Leviner 2018] because effective side branches or collaterals may compensate for the myocardial perfusion in ischemic heart disease for some period of time [Seiler 2013], after which, with the progression of stenosis [Pereg 2014;Tanaka 2016], the clinical symptoms and signs may deteriorate. In our study, the 5-year follow-up of the all-cause mortality and MCEs did not indicate any significant difference between the two groups in regard to those outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All these interventions may not only alleviate the symptoms but also decrease mortality in these patients. 7-12…”
Section: Discussionmentioning
confidence: 99%